Impact of Exchange Rate Volatility on Trade Balance in Nigeria - Oyegun Gbenga; Ofie, Francis Ejime (International Journal on Economics, Finance and Sustainable Development, 2022)
This study explored the relationship between exchange rate volatility and trade balance in Nigeria using annual time series from 1981 to 2020. The study focused on the impact of exchange rate volatility on Nigeria’s balance of trade account, imports, and exports. Exchange rate volatility was measured using GARCH (1,1) variance series derived from the real effective exchange series. Other explanatory variables considered were inflation rate and interest rate, while balance of trade account, imports, and exports were the dependent variables. Error correction models were adopted for the analyses and estimated by the ordinary least squares technique. The findings revealed that exchange rate volatility positively impacts on the balance of trade account, imports and exports in Nigeria with about a very close magnitude. In addition, inflation was very responsive in reducing trade account balance, imports and exports. Although it reduced exports more than it reduced imports. On the other hand, interest rate did not impact on balance of trade and imports but showed a positive impact on exports in Nigeria.